KEDUDUKAN DAN KEWENANGAN PEMERINTAH DAERAH DALAM PELAKSANAAN SISTEM OSS-RBA SEBAGAI SINGLE REFERENCE PERIZINAN BERUSAHA BERBASIS RISIKO PASCA BERLAKUNYA PP NOMOR 8 TAHUN 2025 - Lovresia Melati Siagian; Shannon Gabriela Irene Halim (Cattleya Darmaya Fortuna, 2025)
The introduction of the Risk-Based Online Single Submission (OSS- RBA) system in Indonesia is a major change in the nation’s endeavour to improve the ease of conducting business by means of a simplified, transparent, and technologically advanced licensing procedure. As the implementers of the national policy of single reference under Government Regulation No. 28 of 2025, this study investigates the legal standing and power of local governments within the OSS-RBA framework. In order to investigate the relationship between central and local authorities in the administration of business permits, the study takes a normative juridical approach, concentrating on statutory and conceptual analyses. The results show that while OSS-RBA promotes efficiency and regulatory convergence, it also raises issues with regional governments’ autonomy and the decentralisation concept. The balance between national coordination and regional independence is impacted by the centralised form of the system, which tends to restrict local discretion in dcision-making. Additionally, even though OSS-RBA lowers administrative hurdles and increases legal certainty, its implementation necessitates ongoing local capacity building and harmonisation between national legislation and local administration. The study comes to the conclusion that retaining the constitutional spirit of regional autonomy within Indonesia’s unitary state framework is just as important to OSS-RBA’s success in achieving business convenience as digital transformation.